State-Building, Economic Development, and Democracy : The Japanese Experience - Tsunekawa, Keiichi; Yoshida, Kohei (World Bank, Washington, DC, 2017)
The remolding of the state from an autocratic to a democratic one in postwar Japan is sometimes regarded as a successful case of external intervention for state-building. When Americans landed in Japan two weeks after Japan's acceptance of unconditional surrender, they expected to meet a fanatic and intransigent people. Instead they were surprised by the orderly and peaceful behavior of Japanese soldiers and citizens (Tamaki 2005, 13-20). Disarmament, demobilization, repatriation, and reintegration (into their home towns/villages) of millions of soldiers proceeded surprisingly smooth between 1945 and 1948. The authoritarian state gave way to a democratic one within two years of the beginning of the American occupation and democracy has persisted since1. And finally, the Japanese economy had already begun to experience high growth when the occupation ended in April 1952. In every respect, American occupation policies seem to have been successful. Against this image of the American occupation in Japan, this paper will argue that American policies were only partially helpful in the democratic remolding and economic development of postwar Japan. The prewar political and economic experiences of the Japanese themselves, and the psychological impact of the defeat, played equally important roles in the democratic rebirth of the Japanese state. Those in search of solutions to the development challenges facing fragile countries today should understand that Japan's 'success' did not begin in 1945 and was not the result of a peace settlement quickly followed by new institutions. The ground work for Japanese success was 80-90 years in the making. Analysis of state-building, economic development and democracy in Japan must start from the Meiji restoration of 1868.